Sports health monitoring management system based on artificial intelligence algorithm - Tong, Yunlong; Ye, Lina (Frontiers in Physics, 2023)
With the improvement of people’s material life, more and more people begin to pay attention to health problems. Based on the health field as the main research object, this paper had a certain understanding of the development and current situation of the current health field. Through literature review, it was found that the current health field mainly focused on single monitoring, and systematic health monitoring research was less. Therefore, this paper planed to design a sports health monitoring management system based on artificial intelligence. The system was mainly divided into three modules, which were temperature monitoring module, blood pressure monitoring module and exercise monitoring module. Through these three modules, users’ health data were monitored. In order to ensure the practicability of the system, this paper selected three common living conditions in daily life for experimental detection, namely, the state of exercise, the state of rest and the state of illness. Through the experimental test, under three different living conditions, each monitoring module can operate accurately and normally, which proved that the sports health monitoring management system based on artificial intelligence algorithm designed in this paper was effective and feasible. Through the effective monitoring of each module in different states, relevant data can be obtained. For example, the minimum temperature was 36.5 degrees and the maximum temperature was 37.1 degrees in the exercise state. At rest, the lowest blood pressure was 70, and the highest blood pressure was 80. Each module would read and backup the relevant data and send it to the platform for intelligent analysis. The platform would analyze and compare the data of different modules at the same time, judge the user’s health status at that time, choose whether to send a health alarm for the user, and finally complete the whole system process of the health monitoring management system.